2006
DOI: 10.1126/science.1125548
|View full text |Cite
|
Sign up to set email alerts
|

H5N1 Virus Attachment to Lower Respiratory Tract

Abstract: Highly pathogenic avian influenza virus (H5N1) may cause severe lower respiratory tract (LRT) disease in humans. However, the LRT cells to which the virus attaches are unknown for both humans and other mammals. We show here that H5N1 virus attached predominantly to type II pneumocytes, alveolar macrophages, and nonciliated bronchiolar cells in the human LRT, and this pattern was most closely mirrored in cat and ferret tissues. These findings may explain, at least in part, the localization and severity of H5N1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
511
4
4

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 607 publications
(546 citation statements)
references
References 8 publications
27
511
4
4
Order By: Relevance
“…In contrast, vaccination with MVA-H5 reduced virus replication in both the lower and upper respiratory tract. However, since it is well-established that H5N1 viruses replicate poorly in the upper respiratory tract because of absence of specific receptors (SA-a-2,3-Gal) used by avian influenza virus, it is likely that the virus detected in the upper respiratory tract of H5N1-infected macaques was derived from the lungs (van Riel et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, vaccination with MVA-H5 reduced virus replication in both the lower and upper respiratory tract. However, since it is well-established that H5N1 viruses replicate poorly in the upper respiratory tract because of absence of specific receptors (SA-a-2,3-Gal) used by avian influenza virus, it is likely that the virus detected in the upper respiratory tract of H5N1-infected macaques was derived from the lungs (van Riel et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Influenza A virus primarily infects airway epithelial and antigen-presenting cells by binding to cell surface terminal oligosaccharides on sialic acid residues. Studies have shown that type II cells also express influenza virus receptors (17)(18)(19)(20). In fact, avian influenza H5N1 virus has also been detected in type II cells of humans who died during infection (31).…”
Section: Discussionmentioning
confidence: 99%
“…Influenza A viruses primarily infect cells of the respiratory tract because of the selective binding of viral coat proteins to specific terminal oligosaccharides on sialic acid residues, which in humans and mice are typically found on airway epithelial cells, alveolar type II epithelial cells, and antigen-presenting cells (17)(18)(19)(20). It is generally considered that CD8 1 cytotoxic T lymphocytes (CTLs) are the principal means for viral clearance during a primary AT A GLANCE COMMENTARY Scientific Knowledge on the Subject Despite improved therapies for treating bronchopulmonary dysplasia (BPD), it is unknown why survivors are at increased risk for symptomatic respiratory infections and are often rehospitalized.…”
mentioning
confidence: 99%
“…It has now been reported that avian receptors can be found only in the lower respiratory tract in man, possibly explaining why zoonotic cases up until now have been few 11 , 12 , 13 . Structural studies have demonstrated that just one or two amino acid substitutions at the receptor‐binding region of the HA could change the receptor preference, and this has been seen in the case of occasional isolates of H5N1 viruses from human casees 14 .…”
Section: Introductionmentioning
confidence: 99%